Using heart rate variability to determine individual resistance to the hyperbaric oxygen toxicity - A. S. Samoilov; R V. Nikonov; V. I. Pustovoit; M. S. Kljuchnikov (National Electronic Information Consortium (NEICON), 2020)
Objective: assessment of the resistance of the body of athletes-divers to the hyperbaric oxygen toxicity on indicators of the heart rate variability (HRV). Materials and methods. The study involved 38 healthy athletes-divers aged 23 to 32 years. Before the session of hyperbaric oxygenation (HBO), the test subject was measured the blood pressure and pulse by the method of oscillometry while he was sitting at rest, after which a five-minute recording of HRV in sitting position at rest was made. After that, the two test subjects were placed together, sitting with a physician in a pressure (decompression) chamber, where an absolute pressure of 0.25 MPa was created. The test subjects were given 100 % medical oxygen to breathe, their pulse and blood pressure were measured every 15 minutes, and their cardiac output (CO) was calculated by the Starr formula. When there was an increasing tendency of the CO, and also after 75 minutes of oxygen breathing, the test subjects were taken out of the pressure chamber. Immediately after leaving the pressure chamber, the HRV of the test subjects was recorded. According to the results of measurement of hemodynamic parameters, the test subjects were divided into 3 groups. The first group - unstable, whose CO began to increase in the first 45 minutes of HBO, the second group included those whose CO began to increase from 46 to 75 minutes, the third group included test subjects whose CO did not increase. Results. HRV analysis showed the most significant reliable (p < 0.001) VLF spectrum power (ms2) and relative VLF power (%), as well as Alpha 2 after HBO in the first group of test subjects (unstable) compared to the initial parameters and other groups, which reflects the activation of the sympathetic nervous system and suprasegmental structures of the brain. The essence of changes in the HRV time domain indicators (decrease in SNS index, pNN50 (%), PNS index) confirms the presence of pronounced sympathicotonia in the first group. Conclusions: the three most significant metrics (VLF (ms2), VLF (%) and Alpha 2) were determined with high confidence (p < 0.001), which have a moderate negative correlation (-0.70 < r < -0.30) with the level of divers' resistance to the to the hyperbaric oxygen toxicity. Observations of athletes with high stability showed that they were characterized by changes in hemodynamics of the vagotonic type, while unstable ones were characterized by the sympathicotonic type of regulation. Evaluation of the results showed amoderate correlation between HRV and symptom of oxygen toxicity on divers and is recommended for a reliable (p < 0.05) diagnosis.